SOCIAL STRATIFICATION IN KATHERINE MANSFIELD’S ‘THE DOLL’S HOUSE’: CRITICIAL DISCOURSE ANALYSIS WITH BOURDIEU’S FRAWEWORK - Santa Maya Pramusita (Universitas Sarjanawiyata Tamansiswa, 2021)
This research attempts to reveal the social stratification depicted in the short story entitled ‘The Doll’s House’ by Katherine Mansfield. Qualitative research design with Critical Discourse Analysis (CDA) approach is applied to achieve the research goal. This research focuses on the points of Social Structure, Field, Doxa, Capitals, and Struggle of Pierre Bourdieu. The theme and characters’ interaction will be dissected using the five elements mentioned. In regard to social structure, the finding shows that The Burnell’s family is undoubtedly rich while The Kelvey’s family is poor. The Burnells mingle with other rich people only. They treat lower-class people arbitrarily, that even their new doll’s house is not open for marginalized group. The social fields of this story are Burnell’s house where the interaction between upper-class people takes place, and the school where children with various status levels associate. Meanwhile, the doxas found are the oldest child has more privileges in family, people tend to befriend with those coming from the same social class, and lower-class people are more likely to speak using non-standard English. The Burnell’s daughters and their allies palpably possess economic, cultural, and social capitals. The Kelveys, on the other hand, lack it all. Lastly, the struggles are experienced by Isabel, Kezia, and little Kelveys in obviously different extent.